Catfish Farming with Maggot Feed as a Strategy for Nutritional Sufficiency to Prevent Stunting in Aditirto Village - Rachmadani, Saskia; Isnaeni, Anisa Auliya; Pratiwi, Indah; Palguna, I Gede Bagus Winaka; Apriliani, Siti Aisyah; Faqih, Abdullah; Akhsan, Wahyu Maulana; Pratama, Ardiansyah Surya; Nashita, Marshanda Adelia Putri; Sahila, Diya Rahma; Sofa, Gefira Sahira; Suwarsito, Suwarsito; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Kebumen Regency is still facing high stunting rates, at 9,88% in 2024 (Kebumen Regency Health Office). One solution being implemented is training in catfish farming using maggots as natural feed to increase the availability of animal protein. This initiative aims to educate the community on managing catfish farming using maggots as feed, supporting food security, and meeting family nutritional needs. The training was conducted on August 12, 2025, at the Aditirto Village Hall in Pejagoan District, involving six participants, including the Village Head and fish farming managers. The activity methods included preparation, training, implementation, and evaluation. The results of the activity showed an increase in the community's knowledge and skills in managing catfish farming and maggots as feed, contributing to food self-sufficiency and family nutrition, and is expected to be a sustainable step in addressing stunting in Aditirto Village.